2016
DOI: 10.1002/jaba.300
|View full text |Cite
|
Sign up to set email alerts
|

Multiple schedules in practical application: Research trends and implications for future investigation

Abstract: Researchers began studying multiple schedules in basic laboratories, but recent advances have extended research on multiple schedules to a wide variety of socially significant applications, especially during the last decade. Applied researchers have used multiple schedules (a) to promote stimulus control over high-rate appropriate behaviors, (b) to thin the schedule of reinforcement following functional communication training, and (c) to obtain stimulus control over problem behaviors maintained by automatic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
104
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 96 publications
(239 reference statements)
3
104
0
Order By: Relevance
“…These longer periods did not produce significant increases in destructive behavior. Saini, Miller, and Fisher (in press) reviewed the published literature on multiple schedules and found that among the 52 cases in which schedule thinning was implemented, the terminal schedule of 1 min of reinforcement and 4 min of extinction used by Hanley et al () was achieved in 31 of those published cases (60%). By contrast, we were able to achieve this terminal schedule in 22 of 25 applications (88%), which represents a significantly higher percentage ( Z = 3.24, p < .01) than reported by Saini et al…”
Section: Discussionmentioning
confidence: 99%
“…These longer periods did not produce significant increases in destructive behavior. Saini, Miller, and Fisher (in press) reviewed the published literature on multiple schedules and found that among the 52 cases in which schedule thinning was implemented, the terminal schedule of 1 min of reinforcement and 4 min of extinction used by Hanley et al () was achieved in 31 of those published cases (60%). By contrast, we were able to achieve this terminal schedule in 22 of 25 applications (88%), which represents a significantly higher percentage ( Z = 3.24, p < .01) than reported by Saini et al…”
Section: Discussionmentioning
confidence: 99%
“…Reinforcement schedule thinning is a gradual process of exposing behavior to a leaner schedule of reinforcement that more closely approximates the natural environment in order to establish a more practical treatment (Hagopian, Boelter, & Jarmolowicz, ). For example, after initial stages of FCT when alternative responses produce reinforcement on a dense schedule of reinforcement (e.g., FR 1), experimenters may introduce a multiple schedule in which therapists arrange an alternation between signaled periods of reinforcement availability (S D ) and unavailability (S Δ ; see Saini, Miller, & Fisher, , for a review). A few studies have described response restriction as an approach to schedule thinning in which the alternative response (e.g., exchangeable FCT card) is removed during periods in which reinforcement is unavailable (i.e., S Δ periods; Fisher, Greer, Querim, & DeRosa, ; Roane, Fisher, Sgro, Falcomata, & Pabico, ).…”
Section: Discussionmentioning
confidence: 99%
“…During FCT, a functional communication response (FCR) produces access to the reinforcer for destructive behavior based on the results of a functional analysis (i.e., functional reinforcement), and destructive behavior is placed on extinction. Reinforcement-schedule thinning is a common practice that behavior analysts use to improve the practicality of FCT in natural settings (e.g., home and school; Saini, Miller, & Fisher, 2016). Although FCT typically reduces destructive behavior by more than 95% postreinforcement-schedule thinning (e.g., Greer, Fisher, Saini, Owen, & Jones, 2016), treatment relapse in the form of resurgence often occurs during the thinning process (Briggs, Fisher, Greer, & Kimball, 2018).…”
mentioning
confidence: 99%